2022
DOI: 10.1093/geroni/igac030
|View full text |Cite
|
Sign up to set email alerts
|

Nursing Home Palliative Care During the Pandemic: Directions for the Future

Abstract: Background and Objectives Palliative care addresses physical, emotional, psychological, and spiritual suffering that accompanies serious illness. Emphasis on symptom management and goals of care is especially valuable for seriously ill nursing home residents. We investigated barriers to nursing home palliative care provision highlighted by the COVID-19 pandemic and the solutions nursing home staff used to provide care in the face of those barriers. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Acevedo Rodriguez and colleagues, for example, describe their intervention to increase ACP among a population of veterans diagnosed with COVID-19, through direct telephone calls, which led to a 37% increase in ACP documentation and a 3163% increase in life-sustaining treatment (LST) documentation [ 104 ]. The videoconferencing software Zoom (Zoom Video Communications Inc., San Jose, CA, USA, 2016), was mentioned in numerous papers as a means for facilitating ACP or related educational interventions [ 67 , 83 , 86 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“…Acevedo Rodriguez and colleagues, for example, describe their intervention to increase ACP among a population of veterans diagnosed with COVID-19, through direct telephone calls, which led to a 37% increase in ACP documentation and a 3163% increase in life-sustaining treatment (LST) documentation [ 104 ]. The videoconferencing software Zoom (Zoom Video Communications Inc., San Jose, CA, USA, 2016), was mentioned in numerous papers as a means for facilitating ACP or related educational interventions [ 67 , 83 , 86 , 111 ].…”
Section: Discussionmentioning
confidence: 99%
“… Ninteau and Bishop (2022) look to pandemic experience to understand the supports nursing staff need in their efforts to relieve concerning symptoms for residents, whether on a day-to-day basis or as part of the dying process. Although attention to resident comfort and care goals is intrinsic to every-day nursing care for this high-need population, end of life care is especially crucial, as even during ordinary times 22% of deaths among people aged 65 and older occur in nursing homes ( Centers for Disease Control and Prevention National Center for Health Statistics, 2022 ).…”
Section: Improving Clinical Qualitymentioning
confidence: 99%
“…Three articles ( Bowblis, 2022 ; Kishida, 2022 ; Sharma & Xu, 2022 ) focus on adequacy and stability of staffing, a basic requirement for structural quality. Another group ( Carnahan et al, 2022 ; Cross & Adler-Milstein, 2022 ; Davitt & Brown, 2022 ; Hass et al, 2022 ; Ninteau & Bishop, 2022 ) discuss aspects of clinical care that should be targets for improvement and regulation. And a third group ( Grabowski, 2022 ; Morris et al, 2022 ; Shippee et al, 2022 ) take us beyond what is currently measured and regulated to investigate factors affecting meaning and quality of life for nursing home residents.…”
mentioning
confidence: 99%
“…Development of internal palliative care programs in the PALTC NH setting has been proposed as an answer to the unmet care needs of seriously ill residents 6,20 . This model involves building skills within the NH to promote high-quality palliative care for all residents and holds promise as an effective model 20-22 . A recent scoping review reports the in-house capacity-building model has shown increased family engagement and satisfaction with care, higher documentation of advance care planning, and better documentation of symptom assessment 6 .…”
mentioning
confidence: 99%
“…6,20 This model involves building skills within the NH to promote highquality palliative care for all residents and holds promise as an effective model. [20][21][22] A recent scoping review reports the in-house capacity-building model has shown increased family engagement and satisfaction with care, higher documentation of advance care planning, and better documentation of symptom assessment. 6 Given the potential success of the in-house capacity-building model, a national PALTC organization chose to implement a palliative and supportive care service (PSCS) to enhance the provision of high-quality palliative care to NH residents.…”
mentioning
confidence: 99%